Total internal partition sums for the HITRAN2020 database. (September 2021) - Gamache, Robert R.; Vispoel, Bastien; Rey, Michaël; Nikitin, Andrei; Tyuterev, Vladimir; Egorov, Oleg; Gordon, Iouli E.; Boudon, Vincent
Highlights: Total internal partition sums (TIPS) are reported for 178 isotopologues of 57 molecules important in planetary atmospheres. TIPS are reported from 1 K to a T max that insures the TIPS have converged. The new versions of the TIPS code are available in both FORTRAN and python languages. Abstract: Total internal partition sums (TIPS) are reported for the 181 isotopologues of 57 molecules important in planetary atmospheres. Molecules 1 to 55, with the exception of #34 atomic oxygen, are taken from the HITRAN2020 list, and for some molecules additional isotopologues are considered. Molecules 56 and 57 are C3 H4, CH3, respectively. New to TIPS are the calculations for 12 CH4, 13 CH4, 12 CH3 D, 13 CH3 D, 14 N 16 O, 15 N 16 O, 14 N 18 O, 16 O 32 S 18 O, 33 S 16 O2, 15 N 16 O2, 18 OH, 16 OD, 35 Cl 16 O, 37 Cl 16 O, 16 O 13 C 34 S, 32 S 19 F6, 12 C2 H5 D, 12 C2 H3 D, 12 C 19 F4, 12 CH3 19 F, 70 GeH4, 72 GeH4, 73 GeH4, 74 GeH4, 76 GeH4, 12 CH3 127 I, 13 CH3 127 I, and 14 N 19 F3 . In addition, all the molecules/isotopologues that were not recalculated for TIPS2017 (Gamache et al ., JQSRT 203, 70, 2017) have been recalculated using the 2014 CODATA physical constants. The TIPS are determined by various methods, generally from 1 to 5000 K. These data are provided with HITRAN2020 and a new version of the TIPS code is available in both FORTRAN and python languages. Graphical abstract: Image, graphical abstract